Pengaruh Latihan Small Side Game melalui Mix Method Training terhadap Peningkatan Kapasitas Anaerobik Laktasid - Ghifary, Fathan Insani Alpi Al; Imanudin, Iman; Ugelta, Surdiniaty (Jurnal Simki Pedagogia, 2025)
This study aims to determine the effect of Small Side Game (SSG) training through mixed method training on increasing lactacid an-aerobic capacity in the sport of soccer. This research uses an experimental design with a pre-experimental approach. The research subjects were 50 Persib academy athletes aged 17-18 years. Researchers conducted pre-observation by carrying out an anaerobic lactacid test. The results obtained from initial observations stated that 10 athletes had low anaerobic lactacid levels, so the number of samples used in this study was 10 people and the technique used was purposive sampling. SSG training is applied with variations in intensity and duration, combined with mixed training methods involving anaerobic and aerobic loads. Lactacid anaerobic capacity was measured before and after the intervention using a 150 meter sprint test. Data were analyzed using inferential analysis statistical tests with t-test at a significance level of 5% to determine the significance of changes. The results showed that SSG training through mixed method training significantly increased the lactacid anaerobic capacity of the research subjects (p < 0.05). These findings can strengthen the effectiveness of Small Side Game (SSG) training through mixed method training on an-aerobic lactacid and the basis for developing training programs for coaches to improve athlete performance optimally.